2022
DOI: 10.1186/s12937-022-00822-9
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast during pregnancy and hypertensive disorders of pregnancy in Japanese women: the Tohoku medical megabank project birth and three-generation cohort study

Abstract: Background Hypertensive disorders of pregnancy (HDP) adversely affect the prognosis of mother and child, and the prognosis depends on the subtype of HDP. Skipping breakfast may be associated with increased blood pressure due to disruption of the circadian clock, but the association with the development of HDP has not been studied. The purpose of this study was to examine the association between skipping breakfast and the development of HDP and HDP subtypes in Japanese pregnant women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…During the period of gestation, meal patterning is highly important since pregnant women who sustain prolonged periods of time without food by skipping meals or snacks may be inducing a physiologic stress in their pregnancy [ 39 ]. Even though accidentally skipping a meal is not going to be harmful, skipping meals regularly for different reasons is not advisable to have a better pregnancy outcome [ 40 , 41 ]. Moreover, from different studies, it has been seen that skipping meals during this period is associated decreased dietary quality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the period of gestation, meal patterning is highly important since pregnant women who sustain prolonged periods of time without food by skipping meals or snacks may be inducing a physiologic stress in their pregnancy [ 39 ]. Even though accidentally skipping a meal is not going to be harmful, skipping meals regularly for different reasons is not advisable to have a better pregnancy outcome [ 40 , 41 ]. Moreover, from different studies, it has been seen that skipping meals during this period is associated decreased dietary quality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Singapore had reported that pregnant women had a high prevalence of meal skipping and meal delaying (28% and 29% respectively), and it has been correlated with poor sleep and emotion [10]. Notably, breakfast skipping was examined in most chrononutrition-related studies, as it is the first meal taken in a day [11,12]. Gontijo et al (2018) reported that an earlier breakfast, longer eating window, and more meals taken in a day was associated with improved diet quality during pregnancy, which can be favourable for the mother's health [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the period of gestation, meal patterning is highly important since pregnant women who sustain prolonged periods of time without food by skipping meals or snacks may be inducing a physiologic stress in their pregnancy [39]. Even though accidentally skipping a meal is not going to be harmful, skipping meals regularly for different reasons is not advisable to have a better pregnancy outcome [40,41]. Moreover, from different studies, it has been seen that skipping meals during this period is associated decreased dietary quality [15].…”
Section: Discussionmentioning
confidence: 99%